High-performance surface grating couplers for fiber-chip and free-space coupling - Sánchez-Postigo, Alejandro; Barona-Ruiz, Miguel; Ginel-Moreno, Pablo; Schmid, Jens H.; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Luque-González, José Manuel; Halir, Robert; Cheben, Pavel; Molina-Fernández, Íñigo (My University, 2025)
Surface grating couplers are key components in silicon photonics, as they act as efficient fiber-chip and free-space optical interfaces. Here we review some of our latest advances in these devices, including fiber-chip zero-order grating couplers achieving the highest coupling efficiency–bandwidth product reported to date, single-beam fiber-chip couplers with -0.2 dB coupling loss, single-beam optical antennas yielding nearly 100% directionality and ultra-fast beam steering, and apodized-imaging fiber-chip couplers that focus the radiated light at millimeter-scale distances above the chip surface.
Keywords: Fotónica; Antenas; Óptica integrada; Silicon photonics; Integrated photonics